Re/Assembling the Pregnant and Parenting Teenager Narratives from the Field - Kamp, Annelies; McSharry, Majella (Peter Lang International Academic Publishing Group, 2018)
Drawing in contributions from the United States, the United Kingdom and Republic of Ireland and Aotearoa New Zealand, this book seeks to foreground shifting experiences of teenage pregnancy and parenting in time and space. In the process, the work cuts across enduring 'stigma' contests and dominant discourses which seek to capture, understand and render fixable the 'problem' of teenage pregnancy and parenting, whichever discourse is being privileged.